2006
DOI: 10.1007/bf03194629
|View full text |Cite
|
Sign up to set email alerts
|

Lack of carriers of citrullinaemia and DUMPS in Indian Holstein cattle

Abstract: The present study investigated the occurrence of 2 autosomal recessive genetic diseases, bovine citrullinaemia and deficiency of uridine monophosphate synthase (DUMPS), in Indian Holstein cattle. The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was performed on a group of 642 animals, mainly HF and HF crossbred cattle, to identify carriers of these diseases. None of the animals were carriers of citrullinaemia or DUMPS. It is possible that with the mounting selection pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
15
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 13 publications
6
15
0
10
Order By: Relevance
“…At 0.6% the frequency of FXI-deficiency carriers in the Holstein-Friesian population observed in our study is half that of the 1.2% reported in the Holstein sire population of the USA (Marron et al, 2004). The mutant gene for factor XI deficiency in Indian Holstein-Friesian cattle was higher than citrullinaemia (Murleedharan et al, 1999;Patel et al, 2006) and very much lower than BLAD (Patel et al, 2007), other autosomal recessive genetic diseases observed in Indian Holstein population. Because of the paucity of literature regarding the molecular diagnosis of FXI-deficiency, it is difficult to compare the carrierfrequency in the Indian Holstein-Friesian population to that found in other countries.…”
mentioning
confidence: 38%
“…At 0.6% the frequency of FXI-deficiency carriers in the Holstein-Friesian population observed in our study is half that of the 1.2% reported in the Holstein sire population of the USA (Marron et al, 2004). The mutant gene for factor XI deficiency in Indian Holstein-Friesian cattle was higher than citrullinaemia (Murleedharan et al, 1999;Patel et al, 2006) and very much lower than BLAD (Patel et al, 2007), other autosomal recessive genetic diseases observed in Indian Holstein population. Because of the paucity of literature regarding the molecular diagnosis of FXI-deficiency, it is difficult to compare the carrierfrequency in the Indian Holstein-Friesian population to that found in other countries.…”
mentioning
confidence: 38%
“…Occurrence of mutation in the UMPS gene was reported in Argentina (Poli et al, 1996), Hungary (Fesus et al, 1999) and Taiwan (Lin et al, 2001). Against these reports, there was no carrier of DUMPS in Holstein and native cattles of Turkey (Akyuz et al, 2008), Polish Holstein breed (Kaminski et al, 2005) and Holstein Friesian (HF) and HF crossbred cattle in India (Patel et al, 2006). The complex vertebral malformation (CVM) is a hereditary lethal syndrome in Holstein calves and is characterized by misshapen vertebrae in the cervical, thoracic and lumbar regions of the vertebral column, anomaly of sternum (Nagahata et al, 2002), abnormality of ribs (Revell et al, 2001), low body weight and lateral rotation of the fetlock joints (Duncan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…J. Biotechnol. (Kaminski et al, 2005;Patel et al, 2006). Occurrence of mutation in the UMPS gene was reported in Argentina (Poli et al, 1996), Hungary (Fesus et al, 1999) and Taiwan (Lin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations